Cardiac metastasis in papillary thyroid carcinoma: a case report and literature review - Zhang, Xiaonuo; Huang, Xinyu (Frontiers in oncology, 2025)
Metastasis of malignant tumors to the heart is rare in clinical practice, particularly in papillary thyroid carcinoma (PTC). This report presents the case of a male patient diagnosed with PTC who underwent radical surgery and received I131 treatment. During the fourth year of follow-up, he developed cervical lymph node metastasis. Despite systemic treatment, the patient was hospitalized in the seventh year due to a recurrent cough and expectoration. Anti-infective therapies proved ineffective, and imaging revealed lung metastasis. An echocardiogram identified a hypoechoic mass measuring 5.3 cm by 3.2 cm in the right ventricle, attached to the lateral wall and between the anterior and posterior leaflets, indicating cardiac metastasis. Following diagnosis, the patient’s condition deteriorated rapidly, culminating in death due to heart failure and severe infection. It is well-established that thyroid cancer can metastasize through both hematogenous and lymphatic pathways, with the lungs and brain being the most common sites, followed by the bones and liver. Cardiac metastasis, however, is exceedingly rare, and clinical reports are scarce. This case underscores the importance of considering atypical metastatic sites in advanced thyroid cancer and highlights the aggressive potential of the disease in certain patients. We hope this case raises awareness among oncologists.